(untitled) (LEGAL DIALOGICA, 2025)
The purpose of this study is to find out and analyze the position of workers with diplomas guaranteed as work conditions in the perspective of Law No. 13 of 2003 and to find out and analyze alternative solutions to the problem of diplomas guaranteed as work conditions in the perspective of Law No. 13 of 2003 concerning Manpower. This research is a type of normative legal research that is legal research that is carried out by researching literature materials or legal materials by taking issues from law as a norm system used, normative legal research makes the norm system the center of study. The results of this study can be concluded that related to the detention of the original diploma belonging to the worker, when viewed from existing legal sources, in the labor laws and regulations and the Civil Code there is a legal vacuum related to this matter. On the legal basis of Article 1320 of the Civil Code, which is used, entrepreneurs carry out the act of withholding diplomas based on customs and agreements and freedom of contract in both written and unwritten agreements as legal sources. Abstrak: Penelitian ini memiliki tujuan guna untuk Mengetahui Dan Menganalisis Kedudukan Pekerja Dengan Ijazah Yang Dijamin Sebagai Syarat Kerja Dalam Perspektif UU No. 13 Tahun 2003 Serta untuk Mengetahui Dan Menganalisis Alternatif Penyelesaian Permasalahan Ijazah Yang Dijaminkan Sebagai Syarat Kerja Dalam Perspektif UU No. 13 Tahun 2003 Tentang Ketenaga Kerjaan. Penelitian ini ialah jenis penelitian hukum normatif merupakan penelitian hukum yang dilakukan dengan cara meneliti bahan pustaka atau Bahan Hukum dengan mengambil isu dari hukum sebagai sistem norma yang digunakan maka penelitian hukum normatif menjadikan sistem norma sebagai pusat kajian. Hasil penelitian ini dapat disimpulkan bahwa Terkait Penahanan ijazah asli milik pekerja jika dilihat dari sumber hukum yang ada maka dalam peraturan perundang-undangan ketenagakerjaan dan KUHPerdata terdapat kekosongan hukum terkait hal ini. Atas dasar hukumnya KUHPerdata Pasal 1320 yang digunakan, pengusaha melakukan tindakan penahanan ijazah dengan berdasarkan pada kebiasaan serta kesepakatan dan kebebasan berkontrak dalam perjanjian baik tertulis maupun tidak tertulis sebagai sumber hukumnya.